An individual and community in the light of thenorm of straightforwardness - Dura, Adam (Folia Philosophica, 2001)
The article presents J. Bańka’s conception of ethics in the light of the recent publication titled „The Metaphysical Rap; or a Plea of a Lunatic from Opatów to Other Madmen” („Rap metafizyczny, czyli odezwa wariata z Opatowa do reszty szaleńców”). It also takes into consideration N. Postman’s thesis concerning the triumph of technology over culture (technopol) as well as the postmodernist meanders of normative ethics. The norm of straight forwardness, derived from human nature, is the evidence of trust to the individual who is conscious, mature, “awakened”. The author argues that this norm constitutes the actual alternative to the civilisation structures which deprive the individual of dignity and the possibility of self-realisation. This proposition can be situated on the principle of the coun terpoint to H. Jonas’s ethics of responsibility. On the one hand this proposition accentuates the necessity of the prognostic knowledge about the possible threats and a kind of education sentimantale as the preliminary conditions of ethics while on the other hand - an appeal to conscience and to the simplest feelings constitutive of the straightforward attitude of an individual to values.